Els exempla de Valeri Màxim a la literatura catalana medieval. - CERDÀ, HELENA ROVIRA (Scripta, 2015)
Many works written in Catalan during the XIV and XV centuries transmit several exempla from the Dictorum factorumque memorabilium libri novem of Valerius Maximus. In this paper we include a table with the exact location of 233 episodes in 24 Catalan works. Moreover, we examine more deeply the transmission of these episodes in Felip de Malla's Memorial del pecador remut, the Doctrina compendiosa attributed by some to Francesc Eiximenis and by others to Ramon Soler, the Doctrina moral of Nicolau de Pacs, the Llibre del joc dels escacs of Jacobus de Cessolis, the Recull d'exemples of Arnold of Liége, and some other works with less passages related to Valerius Maximus, as the anonymous Curial e Güelfa, La nau of Lleonard de Sors and the Flors de virtut e de costums translated by Francesc de Santcliment.